MODIFICATION OF BADMINTON LEARNING MEDIA USING TRADITIONAL TOOLS - Hardyanto, Indra; Yono, Topo (Gladi : Jurnal Ilmu Keolahragaan, 2025)
The research method used in this action research is the classroom action research method. This method was chosen because it aims to improve the badminton learning process through modifying learning media using traditional tools. The action research method consists of several main stages, namely problem identification, action planning, action implementation, observation, and reflection. This study is based on the results of a survey and observation at SMK Islam Bustanul Ulum Pakusari, the lack of racket and shuttlecock media makes learning less effective and efficient. Many students do not have rackets and shuttlecocks when learning badminton. This study aims to find out how to modify rackets and shuttlecocks made of wood, boards, newspapers and rope as a solution for badminton learning. The method used defines, interprets, explains a situation. The learning process using modified racket and shuttlecock media is very helpful in overcoming the lack of learning media at SMK Islam Bustanul Ulum.